A forma????o das estrat??gias organizacionais no conselho consultivo de uma holding: A dualidade da estrutura na vis??o da estrat??gia como pr??tica - Marietto, M??rcio Luiz (2014)
This study assumes that the work of social and administrative strategists on Top Level of Organizations, in sociological context, still remain unexplored. One expanding perspective for this kind of research is the Strategy as Practice. The Strategy as Practice provides the categories and levels of analysis when suggested studies of Practitioners, Praxis (Practice), Practices and Strategist Profession (ie, work, workers, tools, consultants, professors, researchers and students of strategy) in organizations with a sociological view. To reach their research objectives the Strategy as Practice had to incorporate into your analytical body sociological theories of ontological and epistemological proximity that could support their intentions and analysis??s interactions for the coherent development of their research. Thus, for this study, we resort to the ontological assumptions of Structurationist Theory. The central dimension of Structurationism is the "Practice", ie, the social practice ordered through time-space. The main arguments fell on understanding the activity of social actors as the central objective of social analysis. In developing the concepts of the Agency, Structure and Duality of Structure theory led to an intrinsic importance to the research of practice of strategic action. Therefore, this study aimed to analyze the social and administrative practices that occur between external consultants and owners of an Advisory Board - Strategic Conduct ??? in recursive interrelation with the structural properties - Duality of Structure - in a large Family Holding that seek social and administrative adjustment for your dynamic durability. To conduct the analysis was used a qualitative research approach. Was used a Multimodal Analysis Methodology making use of three methods of data collection and analysis: Video-based ethnography; In-depth Interview; and Documental Content Analysis. The results demonstrated the operation of Holding??s Advisory Board in the Duality of Organization in order to promote their survival. The analysis also found paradoxical behavior of social actors in the interactions among action and structure. Was also observed that the perspective of social and administrative adjustment to the organization's survival generated uncertainty and culminated in a challenge of dominance for the owners. Finally, was demonstrated that, even paradoxical and complex interactions between social actors of the Advisory Council to be presented, these are imperative features of the recursive movement between action and structure.